The aesthetics of verbal paradox in Qur’anic narratives - touama, achour (El Omda in Linguistics and Discourse Analysis, 2025)
This study tackles the aesthetic of paradox in the Holy Quran based on a kind of formal antagonism. The reader intends to that type of antagonism after conscious contemplative readings based mainly on achieving the mental relationship between the words more than on the tonal or formal relationship. The verbal paradox in the Holy Qur’an tends towards contradicting what is being emphasized to what is actually presented because it needs an alert mind and careful awareness for the Holy Qur’an contemplation. It is considered as a reading skill test between the lines. It is the language of thought, ingenuity, and quickness of mind. This research included a number of Quranic samples and evidence and their analysis and interpretation, depending on the most important and used sources of Quranic interpretation, in order to clarify the aesthetic of verbal paradox, its intentions, surprise, enjoyment, and astonishment. Key words: Aesthetic - paradox - Quranic -Stories - antagonism - astonishment